2021
DOI: 10.1016/j.bj.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electronic cigarette aerosol exposure on oral and systemic health

Abstract: Conventional cigarette smoke harms nearly every organ of the body and is the leading cause of death in the United States and in the world. Decades of research have associated conventional cigarette smoke with several diseases and death. Heavily marketed, electronic nicotine delivery systems such as electronic cigarettes (e-cigarettes) are available in a variety of flavors and high nicotine concentrations. In 2019, a severe lung disease outbreak linked to e-cigarette use led to several deaths, which was called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 82 publications
2
45
0
13
Order By: Relevance
“…Cigarette smoke is harmful [ 1 ] for oral [ 2 , 8 , 37 ] and systemic health [ 2 , 5 , 38 , 39 ] in humans. A systematic review and meta-analysis of 16 articles describing 11,322 COVID-19 patients showed a link between history of smoking and severe cases of COVID-19 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoke is harmful [ 1 ] for oral [ 2 , 8 , 37 ] and systemic health [ 2 , 5 , 38 , 39 ] in humans. A systematic review and meta-analysis of 16 articles describing 11,322 COVID-19 patients showed a link between history of smoking and severe cases of COVID-19 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking harms nearly every organ in the body, and remains the leading cause of preventable disease, disability, and death in the United States [ 1 , 2 ]. Even though the current smoking rates have been declining, in 2019 approximately 34.1 million Americans were currently smoking [ 3 ], especially in the Midwest and South of the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The spotlight of this Biomedical Journal issues goes to a highly informative review by Almeida-da-Silva et al., who summarise the current knowledge regarding risk factors and health effects of e-cigarettes compared to traditional cigarettes [ 13 ] [ Fig. 1 ].…”
Section: Spotlight On Reviewsmentioning
confidence: 99%
“…Without surprises, numerous studies have shown that traditional smoking correlates with modifications to the oral, lung, and gut microbiome, as well as with related diseases such as Crohn's disease and periodontitis [ 16 , 17 ]. Here, the authors focus specifically on the oral microbiome, although the currently available studies have not yet come to a consensus about the effect of e-cigarette use [ 13 ].…”
Section: Spotlight On Reviewsmentioning
confidence: 99%
See 1 more Smart Citation